2017
DOI: 10.3892/ol.2017.6564
|View full text |Cite
|
Sign up to set email alerts
|

Matrine inhibits cell proliferation and induces apoptosis of human rhabdomyosarcoma cells via downregulation of the extracellular signal-regulated kinase pathway

Abstract: Abstract. Matrine, extracted from the Chinese traditional medicine Sophorae flavescentis, has been demonstrated to exhibit antitumor effects on numerous types of cancer in vivo and in vitro with low toxicity. However, its antitumor mechanism in rhabdomyosarcoma (RMS) cells remains unclear. In the present study, the antitumor effects of matrine and its underlying mechanisms in RMS were investigated in vitro. The results demonstrated that matrine inhibited cell proliferation, migration and invasion, and induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Chemotherapeutic agents lead to decreases in cancer cell proliferation through a variety of biological processes, including apoptosis and cellular senescence. In the case of matrine, studies have shown that the molecule induces apoptosis in a variety of cancer cell types . We therefore investigated first whether matrine induced apoptosis in GBM cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotherapeutic agents lead to decreases in cancer cell proliferation through a variety of biological processes, including apoptosis and cellular senescence. In the case of matrine, studies have shown that the molecule induces apoptosis in a variety of cancer cell types . We therefore investigated first whether matrine induced apoptosis in GBM cells.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of matrine, studies have shown that the molecule induces apoptosis in a variety of cancer cell types. [16][17][18] We therefore investigated first whether matrine induced apoptosis in GBM cells. Based on propidium iodide and annexin V staining and the TUNEL assay, the percentage of apoptotic cells did not increase significantly for either cell line treated with matrine (Figures 2A and S2A,C).…”
Section: Matrine Induces Cellular Senescence In Gbm Cellsmentioning
confidence: 99%
“…Matrine can inhibit the proliferation of rhabdomyosarcoma cells by inhibiting ERK signaling pathway and induce apoptosis (Yan et al, 2017). In combination with cisplatin, matrine can downregulate the expression of X-linked IAP (XIAP) and induce the apoptosis of rhabdomyosarcoma RD cells (Li L. et al, 2016).…”
Section: Other Cancersmentioning
confidence: 99%
“…Researches have showed that MEK/ERK signaling pathway plays an important role in regulating cell proliferation, differentiation and apoptosis, thus blocking it can inhibit the proliferation of tumor cells [12].…”
Section: Matrine Inhibits Phosphorylation Signaling Pathways In Cancementioning
confidence: 99%
“…Intensive studies con rmed the anti-tumor mechanisms of matrine, including regulation of phosphorylation of proliferation-and apoptosis-related cell signaling pathways [10,11]. It has been reported that matrine inhibits cell proliferation of human rhabdomyosarcoma cells via inactivation of the ERK signaling [12].…”
Section: Introductionmentioning
confidence: 99%